TRANSITIVITY ANALYSIS OF STUDENTS IN WRITING RECOUNT TEXT AT TENTH GRADE SENIOR HIGH SCHOOL 3 JAMBI CITY - Ayu Ramandha Utami; Khidayatul Munawwaroh; Ridho Praja Dinata (Universitas Batanghari Jambi, 2022)
The objective of the research is to investigate the use of transitivity of students in writing recount text and to find out the most dominant process of transitivity used. In this research, this research used descriptive qualitative method. Subject of the research in this study is students at tenth grade of Senior High School 3 Jambi City in academic year 2021/2022. This research used cluster sampling techniques and as a result the participants in this study is students in class X MIPA 3. The data is collecting by writing test. The data analyzed were 370 clauses taken from recount text written by thirty four students’ X MIPA 3 of tenth grade Senior High School 3 Jambi City. In these clauses, all process types can be found with varieties of the usage. The results were: material process (63%), mental process (15%), behavioral process (8%), verbal process (3%), relational process (5%), and existential process (6%). As for the participants, almost all can be found in students’ recount texts: actor, goal, range, senser, phenomenon, token, value, carrier, attribute, behaver, sayer, verbiage, and existent. Material process is the most process found in the data, it is about 63% or 232 clauses. Material process refers to process of doing and happening. According to Boardman (2008, p. 287) the significant common grammatical patterns of recount text that focused on specific participant, use of material process or action verb, use Circumstance of time and place and temporal sequence of events. The least appear is verbal process.